How does Deep Learning Approach Empowers Extrovert Students to Excel in Writing Communications - Wulan, Cening Ayu; Saputri, Vike Aprilianin Marwintaria; Paramita, Santi; Widiyanto, Widiyanto; Gautama, Sidartha Adi; Ahmad, Tunku Badariah Binti (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2025)
Writing skills are a fundamental component of academic and professional success, enabling effective communication, critical thinking, and knowledge construction. Despite their significance, many students, particularly those learning English as a second or foreign language, face challenges in developing proficient writing abilities. These difficulties are often compounded by individual differences, including personality traits such as introversion and extroversion. While previous studies have explored various pedagogical approaches to enhance writing skills, limited research has focused on how these methods interact with students’ personality types, especially within the context of higher education. This study aims to investigate how a deep learning approach, a pedagogy emphasizing meaningful, mindful, and joyful learning supports and enhances the writing performance of extroverted students compared to introverted ones. The research was conducted with 23 second-semester students from the Buddhist Communication Science Department at Jinarakkhita Buddhist College in Lampung, Indonesia. A mixed-method design was employed, combining pre- and post-writing tests scored using Heaton’s rubric with interviews and personality assessments based on the Eysenck Personality Questionnaire. The findings revealed that the most participants were extroverts, and they demonstrated a significant improvement in overall writing ability after the intervention, particularly in organization and content development. Paired samples t-tests confirmed statistically significant differences between pre-test and post-test scores, indicating the effectiveness of the deep learning strategy for extroverted learners. These results suggest that personality-informed instructional strategies can optimize writing instruction, especially for extroverted students who benefit from interactive and collaborative learning environments. The study contributes to the growing body of research on personalized pedagogy and highlights the importance of aligning teaching methods with students’ psychological profiles to maximize learning outcomes.